Strategi Pemasaran Pariwisata 4A (Attraction, Accessibility, Amenity, Dan Ancillary) Terhadap Minat Wisatawan Mengunjungi Kembali Pantai Camplong Kabupaten Sampang - Wulandari, Oktavia Tri; Jannah, Miftahul (JURNAL ADMINISTRASI & MANAJEMEN, 2023)
In developing natural destinations in the tourism industry, several things need to be considered. Development in tourist destinations can be measured through the level of tourist visits. In tourist attractions, several components must be developed and owned, namely the 4A aspect (Attraction, Accessibility, Amenity, and Ancillary). This study aims to determine the tourism marketing strategy for tourist interest in revisiting Camplong Beach, Sampang Regency, by using component 4A (Attraction, Accessibility, Amenity, and Ancillary) as the variable. Sampling uses nonprobability sampling, and questionnaires are used to collect research data containing statements about variables using a five-point Likert scale. 145 respondents who had visited Camplong Beach were used as research samples. From the results of partial testing (t-test), attractiveness, facilities, and institutions have a considerable (significant) influence on interest in returning to visit. Meanwhile, accessibility did not have a significant influence on interest in revisiting.